Peningkatan Kualitas dan Kuantitas Produksi Pengrajin Jamu melalui Cara Pembuatan Obat Tradisional yang Baik (CPOTB) dan Pengemasan - Sunardi Sunardi; Argoto Mahayana; Widi Hariyanti; Sugiyarmasto Sugiyarmasto; Muhammad Dzakwan (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Traditional medicine / herbal medicine is a product consumed by many people, so the security aspect must be maintained. In order for herbal products to be safely consumed, herbal medicine producers must understand and apply sanitation and hygiene in their production processes and packaging methods. The community service activities aim to improve the knowledge and skills of herbal medicine craftsmen about sanitation and herbal hygiene production and how to pack using continuous sealer machines. This activity was held at PJ SUTI SEHATI, having its address at Pengkol RT 02 RW 1 Nguter Sukoharjo and PJ Bintang Mas having the address at Tenongan RT 2 RW 1 Gupit Nguter Sukoharjo. The form of the activity is providing counseling (lectures and question and answer), training and mentoring. The target of the activity is the leader / owner and employees of herbal medicine craftsmen. The steps of the activity include, preparation, implementation and evaluation. The participants received an explanation of sanitation and hygiene and how to pack using continuous sealer machines. Evaluation has been carried out after service activities which result in packaging using a continuous sealer machine 3-4 times faster and more hygienic.